Pemahaman Konseptual Tentang Hukum Administrasi Negara - Firda Rifdani (Kyadiren, 2020)
This paper tries to describe several differences in terms of administration in public administration. In a broad sense, public administration is often defined as all activities of the state in carrying out its political power, while in a narrow sense, it is an executive activity in carrying out government. This difference implies that the notion of administration in public administration law is different from administration in public administration. It can be concluded that the constitutional law which lays its foundation on the rule of law will always be in contact with administrative law which implements the principle of the rule of law. Conversely, Administrative law always touch on the principle of the rule of law in the implementation of government.